The Story of a long career of varied tasks - Osias, Camilo (Quezon City : Manlapaz Publishing Co., 1971)
Nationals and foreigners have written and published sketches of my life and works. Professionals and students have made researches and studies of my ideas on education, politics, economics, and religion.
Chapter one : I was born in a typical town -- Chapter two : Learning, play, work, worship -- Chapter three : The Beginning of formal schooling -- Chapter four : Studying and teaching -- Chapter five : I Rebel -- Chapter six : Revolution in Earnest -- Chapter seven : People fighting to the bitter end -- Chapter eight : To Vigan -- Chapter nine : Back to Balaoan thence to San Fernando -- Chapter ten : Going to the United States -- Chapter eleven : Three busy, pleasant and fruitful years -- Chapter twelve : Lecturing my way to Columbia University, New York -- Chapter thirteen : Graduate work at teachers' college, Columbia University -- Chapter fourteen : Returning via Europe -- Chapter fifteen : Beginning my public school teaching career -- Chapter sixteen : Superintendent of Bataan, Mindoro, and Tayabas -- Chapter seventeen : Promotion to the directorate -- Chapter eighteen : President of the National University -- Chapter nineteen : Active in politics -- Chapter twenty : Elected resident commissioner to the United States -- Chapter twenty one : Battling for independence in the U.S.A. -- Chapter twenty two : Fighting on several fronts -- Chapter twenty three : Fights on the home front -- Chapter twenty four : Member of the constitutional convention and of the first National Assembly -- Chapter twenty five and twenty six : Loaded with jobs and tasks -- Chapter twenty seven : Imprisoned, accused, vindicated -- Chapter twenty eight : Cultural and spiritual concerns -- Chapter twenty nine : As others see -- Chapter thirty : Recognitions, awards and honors
Include index.
Keywords: OSIAS, CAMILO, 1889-; OSIAS, CAMILO -- POLITICAL VIEWS